Electromyographic study of the trapezius muscle in free movements of the shoulder - Guazzelli Filho, J. [UNESP]; de Freitas, V.; Furlani, J. (Electromyogr Clin Neurophysiol, 1994)
The objective of this study is to analyze the simultaneity of the actions of the three portions of the trapezius (superior portion = TS; middle portion = TM and inferior portion = TI) in elevation, lowering, retraction and protraction of the shoulders. The electromyographic tests were carried out in 20 volunteers using a 4-channel TECA TE 2-7 electromyograph and surface and single coaxial needle electrodes. The electromyographs, obtained with the two types of electrodes, show that in elevation and lowering of the shoulders, TS and TM present increasing and decreasing activity, respectively, from the beginning until the end of these movements. In retraction of the shoulders, TM and TI present increasing activity from the beginning to the end of the movement. In protraction, TS, TM and TI do not show any activity.